Risk of diabetes mellitus (DM) in high school students in Jambi City - Halim, Rd.; Lesmana, Oka; Rudini, Dini; Mulyani, Sri (Proceedings Academic Universitas Jambi, 2025)
Background: Type 2 Diabetes Mellitus (DM) is not only a disease in adults, but is also appearing in teenagers due to changes in lifestyle, eating patterns, and physical activities. Early identification of risk factors for DM in adolescents is important in prevention efforts. The Finnish Diabetes Risk Score (FINDRISC) is widely used to evaluate the risk of type 2 DM through simple parameters such as body mass index (BMI), stomach circumference, physical activity, and family history. Objective: This study aimed to analyze the risk factors for diabetes mellitus type 2 in high school adolescents in Jambi City based on the FINDRISC score. Method: This study used a descriptive quantitative design with a cross-sectional approach. The research sample comprised 414 high school students selected​ using total sampling technique. Data were collected through anthropometry (height, weight, BMI, waist circumference, ) stomach) and a modified version of the FINDRISC questionnaire. Data analysis was performed descriptively using distribution frequency and percentage. Results: Most respondents were aged 16 years (71%) with a balanced sex distribution (50% male and 50% female). As many as 21% were overweight/obese, 11.8% had abnormal stomach circumference, and 62.6% did physical activity ≥ 30 minutes per day, while 53.6% did not consume vegetables or fruits every day. As many as 15.9% of respondents had a history of high blood sugar levels, and 34.6% had a family history of DM. Based on the FINDRISC score, 73.4% were at very low risk, 22% at low risk, 3.1% at moderate risk, and 1.4% at high risk for type 2 DM. Conclusion: Partially big teenagers own risk low against type 2 DM, however there is proportion small with risk medium – high need​ get attention. Contributing factors to improvement risk include Excessive BMI, low physical activity, unhealthy eating patterns, and a family history of DM.